A simulation-based method for the design of supply strategies to enter developing markets. (10th April 2010) - Schwede, Christian; Sieben, Brian; Song, Yu; Hellingrath, Bernd; , Axel Wagenitz
Discrete event simulation is widely applied to support strategic decisions in supply chain design. However, reliable simulation results require highly detailed and precise input data. In many cases, it is costly or even not feasible to gather the required data for the simulation due to the complexity of the situation to be assessed. Furthermore, not all strategically relevant aspects can be considered within a discrete-event simulation of a supply chain. In management science, typologies are commonly being used to support structured and consistent decision making in complex situations. In this paper, we introduce a method that integrates a typology into discrete-event simulation to select appropriate international supply strategies for emerging markets, a field with a high business impact.